Company’s Performance as Measured by the Application of Big Data Analysis Capabilities for Customers - Ramlawati, Ramlawati; Bahari, Andi Faisal; Syahnur, Muh. Haerdiansyah (Jurnal Minds: Manajemen Ide dan Inspirasi, 2022)
Based on an earlier study related to quality and Big Data Analytics, this research seeks to discover the ideas of Technology Utilization, Quality Information, and Talent Quality in affecting Company Performance. The purposive sample consisted of 150 customers from around Indonesia who fulfilled the criteria. SEM-PLS techniques are used to examine preliminary data. Results, the Quality of Information, and talent substantially impact company performance. However, Big Data Analytics does not affect Technology Utilization. These studies may help the company develop its Consumer Big Data analytical skills. Practically, the findings are anticipated to improve the company’s performance to satisfy the demands and desires of customers.